ANALISIS KEMAMPUAN LITERASI SAINS SISWA KELAS VII SMP KOTA PEKANBARU PADA ASPEK KOMPETENSI DAN PENGETAHUAN BERDASARKAN SOAL PISA 2015 - Febrianti, Irma; Arnentis, Arnentis; Syafi’i, Wan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to determine the scientific literacy skills of students ofclass VII in Junior high school Pekanbaru City based on the 2015 PISA questions. Theschools sampled were SMP Negeri 4 Pekanbaru, SMP Negeri 20 Pekanbaru and SMPNegeri 22 Pekanbaru. This research is descriptive quantitative, determining the sampleusing the stratified random sampling technique, namely the sampling technique that isdone when the population is heterogeneous and the total sample obtained is 104students. This type of research data was obtained from the answers to the 2015 PISAquestions given to students. Data was collected by distributing PISA 2015 questionstaken from the e-book Take The Test Sample Question From OECD's PISA Assessmentin Indonesian translation. The 2015 PISA questions containing scientific literacy weretranslated as many as 14 questions containing biological content. Online sample datacollection using Microsoft word and google form. The data analysis technique wascarried out by calculating the percentage of mastery of scientific literacy in the aspectsof competence and knowledge and analyzed descriptively based on the criteria forscientific literacy abilities. To analyze the data on the results of the 2015 PISA questionanswer test, the scoring was done manually using the answer key obtained from thePISA released science item. The results showed that the achievement of scientificliteracy skills of students of class VII SMP Kota Pekanbaru was 24% with very poorachievement criteria.Key Words: Analysis, Scientific Literacy, PISA 2015 Questions